Implementasi Manajemen Pendidikan Multikultural - Humaisi, Syafiq (Jurnal Likhitaprajna, 2020)
The purposes of research are to: (1) know and analyze multiculturalism values developed by the Madrasah Ibtidaiyah Nahdlatul Ulama (MINU), (2) know and analyze the application of multicultural education management in MINU, (3) know and analyze the impact of applying multicultural education management towards the development of MINU. This type of research is qualitative field research. The approach used in this research is the phenomenology approach. which aims to describe the state or phenomenon that occurs. The data collection techniques are (1) in-depth interviews, (2) Observation, and (3) Documentation. The Data Analysis Techniques used are interactive model analysis which consists of three activities, namely; (1) Data reduction (data selection according to a theme); (2) Data display (data presentation); and (3) Conclusion or verification. The results showed that the management of multicultural education management in the area went well with the main learning model based on moving culture class learning / visiting culture.